PENGARUH ROTASI KAP, AUDIT TENURE, SPESIALISASI INDUSTRI KAP, DAN AUDIT CAPACITY STRESS TERHADAP KUALITAS AUDIT DI INDONESIA - Mutia Febriana Azzahra (2021)
This study is a quantitative study that aims to determine the effect of accounting firm rotation, audit tenure, accounting firm industry specialization and audit capacity stress on audit quality. The sample in this study amounted to 65 companies in the mining sector and infrastructure, utilities and transportation sectors listed on the Indonesia Stock Exchange in the 2014-2020 period which were selected based on the purposive sampling method. The data obtained were 65 companies with a total sample of 455. The audit quality in this study was measured using a going concern opinion proxy. The analytical technique used is logistic regression analysis with a significance level of 5%. The results of this study indicate that (1) Accounting firm rotation has no effect on Audit Quality, (2) Audit Tenure has no effect on Audit Quality, (3) Accounting firm Industry Specialization has no effect on Audit Quality, and (4) Audit Capacity Stress has no effect on Audit Quality.